The textbook of spinal surgery - Bridwell, Keith H.; Dewald, Ronald L., 1934- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
Recognized as one of the leading references on the spine, this comprehensive two-volume text brings together experts from around the world to discuss the full scope of spinal surgery. This edition has many new contributors, including both neurosurgeons and orthopaedic surgeons, and presents a broad survey of all aspects of spinal surgery, including degenerative disorders, deformities, tumors, fractures, infections, and more